Rethinking Inclusive Education in Saudi Arabia: Implementation and Cultural Contexts - Alkhunini, Abdulmalik (Journal of International Students, 2026)
This study explores how the concept of inclusion is interpreted and implemented within the context of Saudi Arabian educational policies and cultural contexts, with a focus on the perspectives of Saudi elementary school teachers regarding the challenges involved in adapting Western inclusion models. Through qualitative interviews with five educators working in elementary schools in Riyadh with inclusive education programs, key themes emerged: (a) partial integration of evidence-based practices, (b) caution toward foreign IE materials, and (c) the lack of culturally appropriate and adapted strategies for the implementation of inclusion. The participants’ responses underscore fundamental challenges to transferring foreign frameworks without substantial adaptation and highlight the importance of developing culturally responsive policies. Recommendations include enhancing collaboration between policymakers and educators to support the consistent, sustainable, and equitable implementation of inclusive education in Saudi Arabia.